One-on-one and Door-to-door Learning: Upaya Memaksimalkan Pembelajaran Dari Rumah selama Pandemi Covid-19 - Afib Rulyansah; Rizqi Putri Nourma Budiarti; Emy Yunita Rahma Pratiwi; Nafiah Nafiah; Andini Hardiningrum (Utan Kayu Publishing, 2022)
Probolinggo Regency's primary school-aged children, many of whom have difficulty studying at home owing to the remoteness of the area, would benefit from this community service program. For limited families, this involves aiding kids who don't have the facilities to learn from home, and also encouraging to alleviate the load on families of children who do have the facilities to do so. This exercise consists of six parts: (1) Questions and answers, (2) Examining needs, (3) Design and execution of advice and assistance, (4) Application of assistance, and (5) Monitoring of activity outcomes. Lower-grade pupils have been supported by offering materials for classroom teaching and lending facilities, as well as Media for Instructional Reasons, during the Covid-19 epidemic. Parents are pleased with this mentorship activity. as well as during the worldwide Covid-19 epidemic, while still adhering to health procedure guidelines. Abstrak: Anak-anak usia sekolah dasar di Kabupaten Probolinggo yang banyak mengalami kesulitan belajar di rumah karena letaknya yang terpencil akan mendapat manfaat dari program pengabdian masyarakat ini. Untuk keluarga terbatas, ini termasuk membantu anak-anak yang tidak memiliki fasilitas untuk belajar dari rumah, dan juga mendorong untuk meringankan beban keluarga anak-anak yang memiliki fasilitas untuk itu. Latihan ini terdiri dari enam bagian: (1) Tanya jawab, (2) Meneliti kebutuhan, (3) Merancang dan melaksanakan saran dan bantuan, (4) Penerapan bantuan, dan (5) Pemantauan hasil kegiatan. Siswa kelas bawah telah didukung dengan menawarkan materi untuk pengajaran di kelas dan fasilitas pinjaman, serta Media untuk Alasan Instruksional, selama epidemi Covid-19. Orang tua senang dengan kegiatan bimbingan ini. serta selama epidemi Covid-19 di seluruh dunia, dengan tetap mengikuti pedoman prosedur kesehatan.